2017
DOI: 10.1097/mpg.0000000000001535
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Severe Infusion Reactions Associated With Outpatient Infusion of Infliximab Without Premedications

Abstract: In this report, we describe incremental changes, over a two year period at a single center with the administration of maintenance infliximab infusions. Given practice-driven changes consisting of one-hour infusions and omission of pre-medications, we aimed to investigate if these changes contributed to severe infusion reactions. We reviewed approximately 900infliximab infusions in a pediatric ambulatory infusion center from January 1, 2014-December 31, 2015 for severe adverse reactions requiring either rescue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In the pediatric setting, only few studies have addressed this issue, of which most studies were underpowered. Additionally, most of these studies did not distinguish between different types of PM, so no firm conclusions could be drawn [12,13,18]. A recent retrospective study including a larger cohort of pediatric IBD patients also assessed the influence of PM with corticosteroids, antihistamines, and acetaminophen on risk for IR [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pediatric setting, only few studies have addressed this issue, of which most studies were underpowered. Additionally, most of these studies did not distinguish between different types of PM, so no firm conclusions could be drawn [12,13,18]. A recent retrospective study including a larger cohort of pediatric IBD patients also assessed the influence of PM with corticosteroids, antihistamines, and acetaminophen on risk for IR [19].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in a large cohort study of adult IBD patients receiving IFX, administration of antihistamines as premedication seemed to increase the risk for IR (2.49% vs. 1.32% if not used, p < 0.0001), while corticosteroids did not Premedication with intravenous steroids does not influence the incidence of infusion reactions following infliximab infusions in pediatric inflammatory bowel disease patients-a case-control study seem to significantly influence incidence rates of IR [5]. In children, several small retrospective studies, mostly without the inclusion of a control group, have not confirmed the beneficial effect of PM on the incidence of IR either [12,13]. Overall, there is currently no consensus on the use of PM in pediatric IBD patients to IFX-related IR [14].…”
Section: Introductionmentioning
confidence: 94%
“…A study at Stanford in 2017 yielded no safety concerns over a 2-year period of rapid infliximab infusions. 13 Implementation of rapid infliximab infusion protocols nationwide could result in a considerable amount of freed time for IBD patients. Our QI work at a smaller free-standing children’s hospital suggests rapid improvement is possible with small sustained efforts.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to infliximab, the role of pre-medication is less clear. A randomized trial indicated that pre-medication with betamethasone provided no benefit [ 15 ], while observational studies have yield mixed evidence with respect to benefits of anti-histamines [ 10 , 12 , 16 , 17 ]. Arguably, however, the rarity (9/816) and mild nature of the infusion reactions among patients taking infliximab provide scant impetus to adjust the protocols.…”
Section: Discussionmentioning
confidence: 99%